2001
DOI: 10.4141/a00-044
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing pasture management for cow-calf production: the roles of rotational frequency and stocking rate in the context of system efficiency

Abstract: . 2001. Optimizing pasture management for cow-calf production: the roles of rotational frequency and stocking rate in the context of system efficiency. Can. J. Anim. Sci. 81: 47-56. An experiment was conducted on grass pasture in southwestern Quebec to evaluate the benefits of management intensive grazing (MiG). Sixty-one spring-calving cows, with calves, were assigned to nine treatments, arranged as a 3 × 3 factorial of rotational frequency (RF) (high, 2-d; medium, 6-d; continuous grazing) and stocking rate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Cool‐season grasses require as much as 2.5 times longer for regrowth in summer as they do in spring, a condition commonly referred to as the summer slump (Balasko and Nelson, 2003; Brink et al, 2007; Paine et al, 1996; Smart et al, 1995). Others have reported production peaks early in the growing season with a decline in production as the growing season progresses (Paine et al, 1999; Phillip et al, 2001; Popp et al, 1997). Our results were similar with the notable exception of more summer production under MIRG indicating a positive production benefit to rotational graziers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cool‐season grasses require as much as 2.5 times longer for regrowth in summer as they do in spring, a condition commonly referred to as the summer slump (Balasko and Nelson, 2003; Brink et al, 2007; Paine et al, 1996; Smart et al, 1995). Others have reported production peaks early in the growing season with a decline in production as the growing season progresses (Paine et al, 1999; Phillip et al, 2001; Popp et al, 1997). Our results were similar with the notable exception of more summer production under MIRG indicating a positive production benefit to rotational graziers.…”
Section: Discussionmentioning
confidence: 99%
“…For subhumid systems, what has not been well established is whether stocking rate alone or controlling the distribution of grazing pressure in space and time is beneficial for forage production and quality. In fact, the evidence is equivocal, with some researchers reporting little or no benefit from rotational systems when compared to continuous grazing (Bransby, 1991; Dale et al, 2008; Popp et al, 1997), while others have found production benefits in livestock weight gain and parasite reduction (Papadopoulos et al, 1993), increased pasture productivity (Paine et al, 1999; Fales et al, 1995), and land use efficiency (Phillip et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Rotational grazing may lead to an increase in profitability depending on suitable stocking rates and the frequency of livestock rotation [47,48]. Stocking rate, stocking density, and duration of grazing, coupled with forage biomass and management practices, largely influence ecological conditions and soil health attainment [49].…”
Section: Soil Quality Studies Focusing On Grazed Pasturesmentioning
confidence: 99%
“…Excessive animal grazing creates soil compaction, erosion, nutrient depletion which leads to soil structure degradation, loss of soil carbon and nitrogen, reduced plant diversity and biomass, reduced microbial activity, increased soil acidity [36,37,[39][40][41]49,62]. However, conversion to rotational grazing alone will be insufficient to re-establish a full complement of ecosystem services.…”
Section: Guidance For Cow-calf Producersmentioning
confidence: 99%